2021
DOI: 10.3389/fchem.2021.778896
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid as a Natural Crosslinker for Catalyst-Free Silicone Elastomers From Hydrogen Bonding to Covalent Bonding

Abstract: The construction of silicone elastomers crosslinked by a natural crosslinker under a catalyst-free method is highly desirable. Herein we present catalyst-free silicone elastomers (SEs) by simply introducing tannic acid (TA) as a natural crosslinker when using poly (aminopropylmethylsiloxane-co-dimethylsiloxane) (PAPMS) as the base polymer. The crosslinked bonding of these SEs can be easily changed from hydrogen bonding to covalent bonding by altering the curing reaction from room temperature to heating conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Moreover, the TA exhibited good interfacial affinity with Fe 3+ , which was conducive to the formation of a stable TA/Fe chelate complexes. The pH‐dependent transition between TA and Fe 3+ binding to the dominant TA/Fe structure is shown in Figure 1B 34–36 . Meanwhile, plenty of hydrophilic units (phenol groups) promoted the dispersion of TA/Fe‐BN particles in the NR latex.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the TA exhibited good interfacial affinity with Fe 3+ , which was conducive to the formation of a stable TA/Fe chelate complexes. The pH‐dependent transition between TA and Fe 3+ binding to the dominant TA/Fe structure is shown in Figure 1B 34–36 . Meanwhile, plenty of hydrophilic units (phenol groups) promoted the dispersion of TA/Fe‐BN particles in the NR latex.…”
Section: Resultsmentioning
confidence: 97%
“…The pHdependent transition between TA and Fe 3+ binding to the dominant TA/Fe structure is shown in Figure 1B. [34][35][36] Meanwhile, plenty of hydrophilic units (phenol groups) promoted the dispersion of TA/Fe-BN particles in the NR latex. the BN surface.…”
Section: Resultsmentioning
confidence: 99%
“…43 For the hydrophobic modification of BNNT-TA, aminecontaining alkyl chain molecules, for example, decylamine (DA), were used. 44 Fast agglomeration was observed following the addition of DA to the TA aqueous dispersion of BNNT. The fast agglomeration may be attributed to the increased hydrophobicity of BNNT-TA due to the attachment of DA (Figure 1a; right).…”
Section: Resultsmentioning
confidence: 99%
“…For the hydrophobic modification of BNNT-TA, amine-containing alkyl chain molecules, for example, decylamine (DA), were used . Fast agglomeration was observed following the addition of DA to the TA aqueous dispersion of BNNT.…”
Section: Resultsmentioning
confidence: 99%
“…19 Kong et al demonstrated that aminosilicones would combine with tannic acid (Figure 1) using hydrogen bonding in a simple manner to achieve silicone elastomers linked via hydrogen bonds. 20 We wished to understand if phenolic hydrogen donors 21 � functional groups that are also antioxidants�could be used to make (re)processable silicone elastomers. Such materials would be more sustainable both because of facile reprocessing and the incorporation of natural materials.…”
Section: ■ Introductionmentioning
confidence: 99%